Kebijakan Redaksi Surat Kabar Harian Jogja dalam Pemberitaan Pemilu Pilpres 2024 - Witari, Anggraheni Widya; Muntaha, Ahmad (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
The momentum of the 2024 presidential election is an interesting study to thoroughly explore the editorial policy of Harian Jogja in presenting news. The reference of this research is the editorial policy according to Abrar's opinion (2019). The aim is to find out the editorial policy of Harian Jogja in presenting the news of the 2024 Presidential Election in October-November 2023 by applying a qualitative approach to the case study method and data collection techniques through interviews, observation, and documentation. The results of the study revealed that the editorial policies applied by Harian Jogja are (1)National news sources come from part of the Indonesian Business Group and subscriptions to the Antara News news agency; (2)Harian Jogja strengthens newspaper content in the news through images and infographics; (3)News placement is on the main news page; (4)The character of news writing must include the full name and email of the news writer; (5)Journalists of Harian Jogja must comply with general writing guidelines from PWI, the 5W + 1H principle, have news value, and grammar according to KBBI and PUEBI standards; (6)General policies related to journalistic regulations, guidelines, and rules, such as the Journalistic Code of Ethics and the Press Law.